Development of Online Bakery Shop Web Application (e-Bakery) - Raside, Aini Najwa; Ramli, Azizul Azhar (Applied Information Technology And Computer Science, 2021)
Coronavirus 2019 (COVID-19) has caused a huge economic shock to the public, especially those who do small business. During this period, most sellers will operate on work from home basis to generate income. Mama Reni Enterprise is a business operated by a private bakery seller who runs a homemade business. However, there are some problems encountered such as many people are unaware of the existence of this business due to lack of advertising and also do not know how to place an order. An e-Bakery is a web-based application design with a web-based structured approach. The purpose of developing an e-Bakery to support an online system in expanding advertise on the products in Mama Reni Enterprise. The prototyping model is used as the methodology to develop this system, which will be developed according to the phases of the model until the final system is deployed. This web application was developed in visual studio code using PHP programming language and supported by the XAMPP web server. MySQL database is a database used on the website to record the customer and customer data. At the end of the project, e-Bakery will assist the administrator in handle homemade business with the online website. This system can also help Mama Reni Enterprise’s customers make an order with the new features developed. All the processes in Mama Reni Enterprise can be done easily as their activities have been computerized.